2002
DOI: 10.1046/j.1365-2273.2002.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of otitis media with effusion among children with cleft lip and/or cleft palate1

Abstract: Otitis media with effusion (OME) is common among children with cleft palate, and may lead to such long-term consequences as hearing loss, tympanic membrane retraction, and chronic otitis media (COM). In total, 104 children with cleft lip and/or palate treated for OME at our institution were reviewed. Mean duration of follow-up was 6.9 years, and mean age at latest follow-up was 9.6 years. The incidence of COM was 19%, and the incidence of cholesteatoma was 1.9%. Ears showing such long-term sequelae of OME as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(144 citation statements)
references
References 31 publications
5
129
1
9
Order By: Relevance
“…This is in agreement with the fi ndings of other investigators [3,4,23]. This suggests that Eustachian tube dysfunction, palatine muscle abnormalities and other problems may occur irrespective of the type or side of cleft.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the fi ndings of other investigators [3,4,23]. This suggests that Eustachian tube dysfunction, palatine muscle abnormalities and other problems may occur irrespective of the type or side of cleft.…”
Section: Discussionsupporting
confidence: 93%
“…There was no history of hearing problems obtained from the parents of the participants. Previous studies have documented the absence of clinically signifi cant hearing loss in children with cleft [13][14][15]. Some investigators have, however, commented on varying degrees of hearing loss found in children with cleft palate [4,12,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with CLP may suffer recurrent or continuous OME, causing atelectasis, ossicular fixation, and tympanosclerosis [2,16,17], which can result in conductive hearing loss of up to 30 decibels (dB). Researchers have previously shown that, regardless of whether they have undergone cleft palate repair surgery, as many as 90% of children with CLP suffer from OME or conductive hearing loss, while 50% suffer from recurrent otitis media [2,5,[18][19][20].…”
Section: Consequences Of Ome In Clpmentioning
confidence: 99%
“…Hearing outcomes were evaluated in several case-series studies [16,23,43,[53][54][55][56][57]. Over the long term, between 50 and 94% of CLP children recovered normal hearing after being administered VTI in conjunction with palatoplasty (follow-up 5.5-15.4 years) [16,43,[54][55][56][57].…”
Section: Pre-vti Versus Post-vti Hearing Outcomesmentioning
confidence: 99%